Monetary and fiscal policies, endogenous currency substitution, and exchange rate volatility - Natividad-Carlos, Fidelina B. (The Philippine Review of Business and Economics, 1998)
This paper employs two small, open economy macro models of exchange rate determination - a portfolio balance model and an asset market model - to examine the implications of endogenous currency substitution on exchange rate volatility arising from monetary and fiscal policies. It is shown that, in both models, the exchange rate response and the extent of exchange rate overshooting and undershooting depend on the degree of currency substitution.